2017
DOI: 10.1101/161901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Agrochemical pollution increases risk of human exposure to schistosome parasites

Abstract: Roughly 10% of the global population is at risk of schistosomiasis, a snail-22 borne parasitic disease that ranks among the most important water-based diseases of 23 humans in developing countries 1-3 . Increased prevalence, infection intensity, and spread of 24 human schistosomiasis to non-endemic areas has been consistently linked with water 25 resource management related to agricultural expansion, such as dam construction, which 26 has resulted in increased snail habitat 1,4-6 . However, the role of agroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The predators of the snails investigated in this study include cray fish (Procambarus alleni), water bug (Belostoma flumineum), waterfowl, and cichlid fishes [19,42]. These predators could biomagnify and bioaccumulate certain contaminants during feeding resulting in elevated levels of contaminants in the food chain.…”
Section: Body Burden Of Pollutants In Snailsmentioning
confidence: 99%
“…The predators of the snails investigated in this study include cray fish (Procambarus alleni), water bug (Belostoma flumineum), waterfowl, and cichlid fishes [19,42]. These predators could biomagnify and bioaccumulate certain contaminants during feeding resulting in elevated levels of contaminants in the food chain.…”
Section: Body Burden Of Pollutants In Snailsmentioning
confidence: 99%
“…These researchers missed this finding in their data because they never calculated population growth rates for the snail populations before they reached a carrying capacity or crashed. These results demonstrate that both Syngenta-funded (Herman et al 1986, Baxter et al 2011) and non-Syngenta-funded researchers (Kiesecker 2002, Rohr et al 2011, Halstead et al 2017) have demonstrated that ecologically relevant concentrations of atrazine are capable of increasing snail populations, the source of trematode infections to both amphibians and humans. Given the controversy surrounding the effects of atrazine on amphibians, I now follow this reanalysis with a timeline of some of the most salient events in the history of the atrazine-amphibian controversy.…”
Section: Resultsmentioning
confidence: 62%
“…A mathematical model of schistosomiasis transmission, adapted from the compartmental model developed by Anderson and May [ 19 ] and from other previous work [ 20 , 21 ] (which focused upon S . haemotobium ) is developed to describe parasite burden, measured as mean worm burden per person, W , in the human host population, and three disease states of the intermediate host snail population: susceptible S , exposed (pre-patent, E ) and infectious (patent, I ).…”
Section: Methodsmentioning
confidence: 99%
“…Parameter and state variable descriptions and values used in the model are shown in Table 1 . The transmission parameters, β and λ , representing man-to-snail and snail-to-man transmission, respectively, are estimated by fitting the full model to epidemiological data collected in a community in the Senegal river basin as described elsewhere [ 20 , 21 ]. The aggregation parameter of the negative binomial distribution, κ , is also estimated directly from the data ( S1 Text ).…”
Section: Methodsmentioning
confidence: 99%